ARAH HUKUM EKONOMI DALAM PENGEMBANGAN PEREKONOMIAN INDONESIA - Acep Rohendi (Program Magister Ilmu Hukum Universitas Pancasila, 2019)
Article 33 of the 1945 Constitution, an economic system that is neither socialist nor capitalist. But in practice running the capitalist system which is the forerunner to economic liberalization in Indonesian economic law. The Indonesian economic law is a legal product in the form of laws and regulations which should be an elaboration of Article 33 of the 1945 Constitution. The economic system in the 1945 Constitution is not a capitalist economic system, but a family-based economic system. Pragmatic needs lead to economic liberation so that capitalist-style economic law arises. With the participation of being a member of an international forum / organization forum, which members liberate the economic system. Like it or not the Indonesian state is bound to liberalize its economic system. The need to return to the 1945 Constitution before the amendment is one of the eﬀorts to restore the desired economic system rail Article 33 of the 1945 Constitution. The existence of the GBHN is needed to reformat the capitalistic economic system back to the economic system basedon Article 33 of the 1945 Constitution. Indonesia, which reﬂects the articles of Article 33 of the 1945 Constitution.